The Dorsal Medial Prefrontal Cortex Responds Preferentially to Social Interactions during Natural Viewing - Wagner, Dylan D. (J Neurosci, 2016)
Humans display a strong tendency to make spontaneous inferences concerning the thoughts and intentions of others. Although this ability relies upon the concerted effort of multiple brain regions, the dorsal medial prefrontal cortex (DMPFC) is most closely associated with the ability to reason about other people's mental states and form impressions of their character. Here, we investigated this region's putative social category preference using fMRI as 34 participants engaged in uninstructed viewing of a complex naturalistic stimulus. Using a data-driven “reverse correlation” approach, we characterize the DMPFC's stimulus response profile from ongoing neural responses to a dynamic movie stimulus. Results of this analysis demonstrate that the DMPFC's response profile is dominated by the presence of scenes involving social interactions between characters. Subsequent content analysis of video clips created from this response profile confirmed this finding. In contrast, regions of the inferotemporal and parietal cortex were selectively tuned to faces and actions, both features that often covary with social interaction but may be difficult to disentangle using standard event-related approaches. Together, these findings suggest that the DMPFC is finely tuned for processing social interaction above other categories and that this preference is maintained during unrestricted viewing of complex natural stimuli such as movies. SIGNIFICANCE STATEMENT Recently, studies have brought into question whether the dorsal medial prefrontal cortex (DMPFC), a region long associated with social cognition, is specialized for the processing of social information. We examine the response profile of this region during natural viewing of a reasonably naturalistic stimulus (i.e., a Hollywood movie) using a data-driven reverse correlation technique. Our findings demonstrate that, during natural viewing, the DMPFC is strongly tuned to the social features of the stimulus above other categories. Moreover, this response differs from other areas with previously well characterized response profiles such as the lateral and medial fusiform gyrus. These findings suggest that this region's dominant function in everyday situations is to support reasoning about the thoughts and intentions of conspecifics.